(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Creep deformation is one of the life time limiting reasons for gas turbine parts that are subjected to stresses at elevated temperatures. In this study, creep rupture behavior of uncoated and coated Rene®80 (a nickel-based superalloy-GE trademark) by platinum-aluminide (Pt-Al) was evaluated in air under constant load conditions using combinations of temperature and stress namely 760°C/657 MPa, 871°C/343 MPa and 982°C/190 MPa. For this purpose, an initial layer of platinum with a thickness of 6µm was applied on the creep specimens. Then, Low Temperature-High Activity (LTHA) and High Temperature-Low Activity (HTLA) methods were used for aluminizing. The results of microstructure and phase analysis by SEM/EDS and XRD showed a dual-phase/three-layer structure of the coatings. Results of creep-rupture tests showed a decrease in resistance to creep rupture of coated specimen, compared to the uncoated ones. The reductions in rupture lives in LTHA and HTLA methods at 760°C/657 MPa, 871°C/343 MPa and 982 °C/190 MPa were almost (26% and 41.8%), (27.6% and 38.5%) and ( 22.4% and 40.3%), respectively as compared to the uncoated ones. However, HTLA aluminizing method showed an intense reduction in creep life. Results of fractographic studies on coated and uncoated specimens indicated a combination of ductile and brittle failure mechanisms for all samples. Although, the base failure mode in substrate was grain boundary voids, cracks initiated from coating at 760°C/657MPa and 871°C/343. No cracking in the coating was observed at 982°C/190MPa.